Gender Integration in Sheep Fattening: A Training Manual (Amharic) - Ekule, Muluken; Wamatu, Jane; Asefa, Getu; Mengiste, Elsa; Belayneh, Tesfa (International Center for Agricultural Research in the Dry Areas, 2022)
A training manual on Gender Integration in Sheep Fattening (Amharic).